A morada paulista moderna: espaços interiores nas residências de João Batista Vilanova Artigas - Perpétuo, Daniela (2012)
This research is concentrated on the issue of modern architecture in São Paulo, with primary focus on interior architecture, and a study case of four homes selected of the Brazilian architect João Batista Vilanova Artigas, analyzing its architecture and interior configuration, and the set of elements, which create the "atmosphere" of settings. The four homes that will be more closely analyzed are: the "Cottage" ( Casinha ), from 1942; the Second House of the Architect, from 1949; Olga Beata s House, from 1957, and Elza Berquó s House, from 1967. Other homes will also be studied, such as Rubens de Mendonça s House, or Triangles s house, from 1959; the Telmo Porto s house, from 1968, and Martirani s house, from 1974. The analyzis will be performed from the comparison of photographic sources from different times. Each set of users, at different times, helped set up the arrangement of the rooms in different ways, which allows to indirectly check their interference in the internal arrangements of the houses.